Delivery of biannual ultrasound surveillance for individuals with cirrhosis and cured hepatitis C in the UK. (20th February 2023) - Hamill, Victoria; Gelson, Will; MacDonald, Douglas; Richardson, Paul; Ryder, Stephen D.; Aldersley, Mark; McPherson, Stuart; Verma, Sumita; Sharma, Rohini; Hutchinson, Sharon; Benselin, Jennifer; Barnes, Eleanor; et al.
Abstract: Background: Previous studies show the uptake of biannual ultrasound (US) surveillance in patients with cirrhosis is suboptimal. Here, our goal was to understand in broader terms how surveillance is being delivered to cirrhosis patients with cured hepatitis C in the UK. Methods: Hepatitis C cirrhosis patients achieving a sustained viral response (SVR) to antiviral therapies were identified from the national Hepatitis‐C‐Research‐UK resource. Data on (i) liver/abdominal US examinations, (ii) HCC diagnoses, and (iii) HCC curative treatment were obtained through record‐linkage to national health registries. The rate of US uptake was calculated by dividing the number of US episodes by follow‐up time. Results: A total of 1908 cirrhosis patients from 31 liver centres were followed for 3.8 (IQR: 3.4–4.9) years. Overall, 10 396 liver/abdominal USs were identified. The proportion with biannual US was 19% in the first 3 years after SVR and 9% for all follow‐up years. Higher uptake of biannual US was associated with attending a liver transplant centre; older age and cirrhosis decompensation. Funnel plot analysis indicated significant inter‐centre variability in biannual US uptake, with 6/29 centres outside control limits. Incident HCC occurred in 133 patients, of which 49/133 (37%) were treated with curative intent. The number of US episodes in the two years prior to HCC diagnosis was significantly associated with higher odds of curative‐intent treatment (aOR: 1.53; 95% CI: 1.12–2, 09; p  = .007). Conclusions: This study provides novel data on the cascade of care for HCC in the UK. Our findings suggest biannual US is poorly targeted, inefficient and is not being delivered equitably to all patients.